Pengaruh Senam Otak Terhadap Tingkat Kejenuhan dan Tingkat Motivasi Belajar Mahasiswa STIKES Telogorejo Semarang - Linda Kusuma Anggakristi; Prita Adisty Handayani; Elis Hartati (Indonesian Journal of Nursing Research (IJNR), 2021)
Community nursing care is a nursing service provided to improve the degree of health that focuses on the community including individuals, families, groups & communities. Nurses as educators also play a role in the higher education environment with the youth community. Teenagers (students) have learning demands for self-development to prepare for the future. The demands faced today are bigger than what they had during high school. This demand often makes students bored, not interested in attending lessons (rowdy), and loses motivation. This study aims to determine whether brain exercise has an effect on the level of boredom and the level of learning motivation in STIKES Telogorejo Semarang students. The hypothesis in this study is that there is an effect of brain exercise on the level of boredom and the level of learning motivation in STIKES Telogorejo Semarang students. The subjects in this study were 47 students of the sixth semester of the S-1 Nursing study program at STIKES Telogorejo. The type of research used is Quasy Experiment with one group pretest - posttest. The data collection tools used were the MBI-SS (Maslach Burnout Inventory- Student Survey) questionnaire and the motivation scale. Data analysis was performed univariate and bivariate (using the Wilcoxon test p <0.05). The results of this study indicate that the hypothesis is accepted, there is an effect of brain exercise on the level of boredom by obtaining a value of p =0.009 (<0.05) and there is an effect of brain exercise on the level of learning motivation in STIKES Telogorejo Semarang students with p = 0.000 (<0.05).